Ta’zir dan Kewenangan Pemerintah dalam Penerapannya - Azhari Akmal Tarigan (Universitas Islam Negeri Jakarta, 2017)
This article examines the issue of jarīmah ta'zīr as one of the dimensions of Islamic criminal law which has flexibility in its application.In contrast to ḥudūd and qisāṣ whose rules are very clear and detailed in the Qur'an, ta'zīr is not set clearly in the Qur'an. Therefore, the ijtihad of a ruleror judge to determine the type of crime and jarimah that can be punished (ta'zīr) and the type and form of punishment is really important. The flexibility of ta'zīr allows to accommodate the complex form of crime suchas gratification, corruption, sexual harassment, drugs, and pornography.But ta'zīr also opens the opportunity for the tyranny of the government inpunishing a person. This article offers the need for ta'zīr by making qanun like in Aceh. DOI: 10.15408/ajis.v17i1.6223